Essentials of Testing and Assessment, 3rd Edition - Edward S. Neukrug; R. Charles Fawcett (Cengage Learning, 2019)
Neukrug and Fawcett's ESSENTIALS OF TESTING AND ASSESSMENT: A PRACTICAL GUIDE FOR COUNSELORS, SOICAL WORKERS, AND PSYCHOLOGISTS, ENHANCED, 3rd Edition, offers a comprehensive and easy-to-read introduction to the concepts and applications of assessment and testing. Case vignettes, samples of real tests, and additional activities and exercises help you grasp and understand the material.